Confronting the Challenges of Journalism Education in Rwanda in the context of Educational Reforms - Jjuuko, Margaret; Njuguna, Joseph (Scholarship of Teaching and Learning in the South, 2019)
Policy reforms aimed at improving access to and equity in tertiary education have meant that university classes are not only larger, but more diverse in terms of students’ competencies and experiences. Despite the increase in the size and diversity of student populations in universities, the financial, technological and human resources have not expanded at a similar rate, leaving academic programs struggling to improve the quality of educational experience, whilst teaching more students with less resources. This is particularly difficult in practice-based disciplines such as medicine, nursing and journalism, where coaching models and small-class learning experiences are seen as being the most effective way of nurturing work-ready graduates. Teaching journalism under these conditions is particularly problematic because of the dynamic changes being experienced across the media industries as a result of technological change and the changing media ecosystem.
Keywords: Journalism education; practical theory of journalism education; scholarship of teaching and learning; global south